Noncanonical Role of Telomerase in Regulation of Microvascular Redox Environment With Implications for Coronary Artery Disease. Issue 5 (3rd September 2022) - Ait-Aissa, K; Norwood-Toro, L E; Terwoord, J; Young, M; Paniagua, L A; Hader, S N; Hughes, W E; Hockenberry, J C; Beare, J E; Linn, J; Kohmoto, T; Kim, J; et al.
Abstract: Telomerase reverse transcriptase (TERT) (catalytic subunit of telomerase) is linked to the development of coronary artery disease (CAD); however, whether the role of nuclear vs. mitchondrial actions of TERT is involved is not determined. Dominant-negative TERT splice variants contribute to decreased mitochondrial integrity and promote elevated reactive oxygen species production. We hypothesize that a decrease in mitochondrial TERT would increase mt DNA damage, promoting a pro-oxidative redox environment. The goal of this study is to define whether mitochondrial TERT is sufficient to maintain nitric oxide as the underlying mechanism of flow-mediated dilation by preserving mt DNA integrity.Immunoblots and quantitative polymerase chain reaction were used to show elevated levels of splice variants α- and β-deletion TERT tissue from subjects with and without CAD. Genetic, pharmacological, and molecular tools were used to manipulate TERT localization. Isolated vessel preparations and fluorescence-based quantification of mt H2 O2 and NO showed that reduction of TERT in the nucleus increased flow induced NO and decreased mt H2 O2 levels, while prevention of mitochondrial import of TERT augmented pathological effects . Further elevated mt DNA damage was observed in tissue from subjects with CAD and initiation of mt DNA repair mechanisms was sufficient to restore NO-mediated dilation in vessels from patients with CAD. The work presented is the first evidence that catalytically active mitochondrial TERT, independent of its nuclear functions, plays a critical physiological role in preserving NO-mediated vasodilation and the balance of mitochondrial to nuclear TERT is fundamentally altered in states of human disease that are driven by increased expression of dominant negative splice variants.